An Energy Supply System for Wireless Sensor Network Nodes. (23rd May 2012) - Zheng, Guoqiang; Zhang, Liwei; Li, Jishun
Abstract : The power source is a critical obstacle for wireless sensor network nodes. In order to prolong the lifetime of wireless sensor networks, this paper presents an energy supply system that uses a specially designed broadband piezoelectric energy harvesting technology for sustaining the operation of wireless sensor network nodes. The proposed energy supply circuit can apply an optimal control voltage to the piezoelectric element to ensure impedance matching between the vibration source and the energy supply system in nonresonance frequencies. As compared to the conventional piezoelectric energy harvesting circuit, it is shown that the efficiency has been increased 4 times. In this work, the overall system structure, the function modules design, and the performance testing analysis are illuminated in detail. Experimental results reveal that this energy supply system can significantly improve power within the wide bands by the active piezoelectric energy harvesting technology and enable wireless sensor network nodes to operate normally.